1996
DOI: 10.1021/jm960038f
|View full text |Cite
|
Sign up to set email alerts
|

4-[4-[(2-Hydroxybenzoyl)amino]phenyl]butyric Acid as a Novel Oral Delivery Agent for Recombinant Human Growth Hormone

Abstract: A series of N-acetylated, non-alpha, aromatic amino acids was prepared and shown to promote the absorption of recombinant human growth hormone (rhGH) from the gastrointestinal tract. Seventy compounds in this family were tested in vivo in rats. Of the compounds tested, 4-[4-[(2-hydroxybenzoyl)amino]phenyl]butyric acid was identified as a preclinical candidate and was used to demonstrate the oral delivery of rhGH in primates. A significant positive correlation was found between the relative log k' of the delive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
51
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 65 publications
(52 citation statements)
references
References 16 publications
1
51
0
Order By: Relevance
“…As was presented in Chart 1, employment of phase transfer catalyst benzyltriethylammonium chloride (TEBA) gave 4-(2-acetoxy-benzoylamino) butyric acid with an increasing yield of 85% based on the earlier reported procedures, [38][39][40][41][42] in which acylation reaction of the starting material GABA handled with trimethylchlorosilane (TMSCl) and 2-(acetyloxy)benzoyl chloride led a yield of 39.9% in dichloromethane, or a yield of 33.7% after crystallization with ethanolwater in presence of aqueous medium sodium hydroxide.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…As was presented in Chart 1, employment of phase transfer catalyst benzyltriethylammonium chloride (TEBA) gave 4-(2-acetoxy-benzoylamino) butyric acid with an increasing yield of 85% based on the earlier reported procedures, [38][39][40][41][42] in which acylation reaction of the starting material GABA handled with trimethylchlorosilane (TMSCl) and 2-(acetyloxy)benzoyl chloride led a yield of 39.9% in dichloromethane, or a yield of 33.7% after crystallization with ethanolwater in presence of aqueous medium sodium hydroxide.…”
Section: Resultsmentioning
confidence: 96%
“…General Procedure for the Synthesis of 1a [38][39][40] A: Preparation of 2-Acetoxy Benzoyl Pyrrolidone (1.3a) 48) Benzyltriethylaminium chloride (TEBA) (0.005 mol) was added to the pyrrolidone sodium salt (1.2a) (0.05 mol) dissolved in the anhydrous toluene solution below 10°C and c 7 (0.05 mol) in anhydrous toluene was added dropwise. Then reacted at room temperature for 0.5 h and at 50°C for 3 h. Water (100 mL) was added and saturated sodium bicarbonate was mixed to wash the toluene layer with 20 mL, 20 mL, 10 mL, respectively, and then the suspension was washed until neutral with water (50 mL), dried over anhydrous magnesium sulfate overnight and crystallized with ethanol to precipitate the product 10.…”
Section: Methodsmentioning
confidence: 99%
“…These molecules are usually unstable in the intestinal environment, because they are susceptable to acid hydrolysis, enzymatic degradation, and bacterial fermentation, which prevents their effective delivery. 1,2 Moreover, because of the size, charge, and/or hydrophilicity of these macromolecular drugs, transport through the intestinal epithelium is poor. 3 Thus, these drugs can only be effectively administered parenterally at present.…”
Section: Introductionmentioning
confidence: 99%
“…[13][14][15][16][17][18][19] We have synthesized delivery agents based on N-acylated ␣-amino acids 20 and n-acylated non-␣-amino acids 21 and demonstrated in animal models that they promote oral absorption of macromolecules. N- [8(-2-hydroxybenzoyl) amino]caprylate (SNAC)-mediated gastrointestinal absorption of heparin occurs in a passive transcellular process, 22 without causing apparent damage to intestinal epithelium.…”
mentioning
confidence: 99%
“…24 Investigations, both in vitro and in vivo, revealed that the n-acylated non-␣-amino acid SNAC has no pharmacological activity. 21 However, it increased aPTT in primates dosed orally with heparin. Hypoglycemia, nausea, and emesis were observed at high doses (1800 mg/kg) of SNAC with an unformulated solution in cynomolgus macaques.…”
mentioning
confidence: 99%